A transformação da cozinha dentro dos apartamentos na cidade de Vitória, Espírito Santo: a ascensão do gourmet na virada do século - Erick Alessandro Schunig Fernandes; Paulo César Scarim (Confins)
This study analyzes aspects that involve the relation between the kitchen and the transformations in the urban space in the city of Vitoria, Espírito Santo, at the beginning of this century. The city has been undergoing an intense process of transformation resulting from the action of the real estate construction sector for housing, which presents a lifestyle in apartments. Over the last decade, this sector has been establishing strategies aimed at increasing its income, in which it started to use the gourmet as a sign that aims to establish a connection between food and space in terms of social distinction. The kitchen is inserted in this strategy from its re-signification as food space in housing in apartments. From the theoretical contribution of authors and the analysis of real estate advertisements in a large newspaper, it was possible to find indicatives that show the relationship between the changes in this domestic item and our daily life and the introduction of a new relationship with food.